2000
DOI: 10.1007/s11664-000-0089-1
|View full text |Cite
|
Sign up to set email alerts
|

The hall mobility and its relationship with persistent photoconductivity of undoped GaN

Abstract: Special Issue PaperHall effect measurements have been widely used to characterize electrical properties of undoped and doped GaN. 1,2 The Hall mobility is indicative of electrical quality of undoped GaN in optimization of growth conditions. 3,4 Although a number of models have been proposed to explain anomalous behavior of the Hall mobility dependency on the electron density, 5-7 mechanism, which dominates the Hall mobility of undoped GaN, still remains unclear. The yellow-band luminescence (YL) and persistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The electrons travel a short distance if they recombine along the outmost edge of the LED mesa; thus the edge emission can be still obvious (Figure g). However, as the electron mobility in n-GaN can be quite high (hundreds of cm 2 ·V –1 ·s –1 ), the radiative recombination is not limited to the edge of the LED mesa, as corroborated by the appearance of green light within the contour of the LED under reverse bias (Figure b). The nonhomogeneity of the emission across the LED mesa may be caused by the nonuniform distribution of recombination centers as well as nonuniform current spreading across the ZnO layer, which needs to be improved.…”
Section: Resultsmentioning
confidence: 86%
“…The electrons travel a short distance if they recombine along the outmost edge of the LED mesa; thus the edge emission can be still obvious (Figure g). However, as the electron mobility in n-GaN can be quite high (hundreds of cm 2 ·V –1 ·s –1 ), the radiative recombination is not limited to the edge of the LED mesa, as corroborated by the appearance of green light within the contour of the LED under reverse bias (Figure b). The nonhomogeneity of the emission across the LED mesa may be caused by the nonuniform distribution of recombination centers as well as nonuniform current spreading across the ZnO layer, which needs to be improved.…”
Section: Resultsmentioning
confidence: 86%
“…Mobility enhancement after illumination in semiconductor systems has been reported by several groups [25][26][27][28][29][30]. due to photoexcitation at a fixed temperature can be attributed to the increased electron mean energy with the increasing carrier density in the 2DEG channel, which results in a less efficient interaction of the 2DEG electrons with the ionized donor impurities as well as improved screening [25,27].…”
Section: Resultsmentioning
confidence: 95%
“…The nature of several defects and their effects on the optical and transport properties of GaN are not well understood. For example, (i) an anomalously long relaxation time of photoexcited carriers is commonly observed in GaN [3][4][5][6][7][8][9][10], but so far the microscopic origin of this phenomenon is not understood; (ii) extended defects, like a grain boundary or dislocation, are commonly observed in GaN [2],…”
Section: Introductionmentioning
confidence: 99%
“…A columnar structure is often observed in transmission electron micrographs [2]. Grain-boundary induced potential fluctuation has been used to explain the anomalous Hall results [10,[13][14][15] of the dependence of mobility on carrier concentration and anomalous conductivity results [16] in the ion-implanted epitaxial layer. Wang et al [10] have shown that Hall mobility in undoped GaN is related to the long relaxation time of photoexcited carriers due to the presence of a charged dislocation-point-defect complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation